Ansiedad en familiares de pacientes hospitalizados en la Unidad de Cuidados Intensivos (UCI) del Hospital General Isidro Ayora de la ciudad de Loja. - Morocho Cabezas, Israel Fernando (2018)
The anxiety-state is defined as "a condition or transient emotional state of the human organism, which is characterized by feelings of subjective tension and perceived apprehension consciously, and by an increase in the activity of the autonomic nervous system." The trait-anxiety "refers to the relatively stable individual differences in the propensity to anxiety that is, to the differences among people in the tendency of responding to perceived situations as threatening. It is a study which is descriptive and transversal. 51 relative members of hospitalized patients participated in the Unidad de Cuidados Intensivos del Hospital Isidro Ayora (30 women and 21 men) of legal age. The score obtained according to the IDARE INVENTORY guidelines showed that there is a high level of anxiety-state with 50.98% of female participants, and a high level of anxiety in male people with a 25.49%, and also evidence that there is a medium level of anxiety-trait in women with 29.41%; and of the male sex there is also a medium level of anxiety-trait with 25.49%. The objectives were reached: to determine the level of anxiety-trait and anxiety-state in relatives of patients hospitalized in the Unidad de Cuidados Intensivos. Regarding the Anxiety-State level, it was observed that in both sexes the high level of anxiety predominates with 50.98% in female participants and 25.49% in male people, in which refers to the Anxiety-Trait level, it was shown that there is a average level of anxiety since anxiety for women with 29.41% and for male people with 25.49%. The major number of participants was women with 58.82%, regarding the relativeness of patients who are hospitalized in UCI, the most are sisters and children. Keywords: Anxiety, relatives, hospitalization, ICU, patients.